Environmental Life Cycle Assessment of Healthcare Waste Valorisation Alternatives - Zlaugotne Beate; Zandberga Anda; Gusca Julija; Kalnins Silvija Nora (Environmental and Climate Technologies)
Infectious healthcare waste (iHCW), after microbial inactivation treatment, primarily ends up in landfills. Although the morphological composition of iHCW depends on the type of health facility, predominantly HCW consists of plastic and textile waste. Furthermore, after the treatment iHCW is cleaner from a microbiological contamination perspective than household waste, making it a highly valuable resource. Recycling iHCW has environmental and economic benefits and by valorising iHCW, it would be possible to reduce the amount of landfilled waste and use it as a resource. The aim of the research is to understand the environmental consequences and potential benefits of treated iHCW valorisation scenarios through the ‘gate-to-gate’ (from iHCW generation at medical facilities to end-of-life or recovery) life cycle assessment framework and to compare it with the existing practice – landfilling with functional unit 1 ton of treated iHCW and using ReCiPe 2016 (Midpoint, Hierarchist perspective) method. Valorisation scenarios (VS) analysed the use of treated HCW as a substitute of feedstock for reinforced asphalt, reinforced cement, RDF, syngas, acoustic panel and plastic components used for hydroponics. The results of the LCA demonstrate that from the environmental impact perspective, the best scenarios are syngas production (VS4) with cumulative result −11Pt and −237 kg CO2 eq for global warming impact category and RDF (VS3) with result −5Pt and −195 kg CO2 eq for global warming impact category, as the entire iHCW flow is recycled into energy. However, when recycling waste, the most valuable product must be created, and then the best results from plastic recycling are plastic components for hydroponics (VS6) with result 50Pt and 1181 kg CO2 eq for global warming impact category and reinforced asphalt (VS1) with result 53 Pt and 1246 kg CO2 eq for global warming impact category. From textile recycling acoustic panels (VS5) with result 55 Pt and 598 kg CO2 eq for global warming impact category and reinforced cement (VS2) with result 55 Pt and 603 kg CO2 eq for global warming impact category. Therefore, additional scenario was created where plastic, textile and residual iHCW streams are fully recycled and fully eliminating landfilling. The results show that BAU with result 75 Pt and 1509 kg CO2 eq for global warming impact category has the greatest environmental impact compared to any of the VS considered in this research. Of the total scenario impacts, the largest impact is caused by waste disposal, followed by transport, which has a similar impact in all scenarios due to assumptions about the distance to be transported, and iHCW treatment also has a similar impact in all scenarios, but the bigger difference is the environmental benefit from recycled waste. Based on the LCA results, recommendations for the stakeholders are developed.